THE DISEASE INDUSTRY AND HEALTH IN DISPUTE IN BRAZIL - Rosevaldo Ferreira da Silva, Antonio (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the structural contradictions of the Brazilian healthcare system, contrasting the universal and public nature of the Unified Health System (SUS) with the growing influence of the medical-industrial-financial complex, which transforms disease into a commodity. The research highlights how chronic underfunding, fiscal austerity policies, and the privatization of hospital management weaken the SUS and favor market logic. It also discusses the historical neglect of tropical diseases and the subordinate role of national scientific research in the face of the corporate interests of the pharmaceutical industry. The study concludes that defending the universal right to health requires strengthening public funding, investing in science driven by social needs, and expanding popular participation in sector decisions.